PENGARUH KOMPETENSI, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM BINA MARGA KABUPATEN MUSI RAWAS - Sutanta, Sutanta; Fahmi, Muhammad (LPPM UNIVERSITAS BINA INSAN, 2019)
This study aims to determine the effect of competence, compensation, and motivation on employee performance at the Public Works Department of Musi Rawas, both simultaneously and partially. The research sample of 60 respondents, and data collection through questionnaires. Analysis of the data used is descriptive quantitative. The results showed that there was a significant influence between competency, compensation and motivation together on employee performance as evidenced by the value of Fcount = 38.881> Ftable = 2.77. There is a significant effect between competency and motivation together on employee performance as evidenced by the value of Fcount = 43.953> Ftable = 3.16. There is a significant influence between competence and compensation together on employee performance as evidenced by the value of Fcount = 38.763> Ftable = 3.16. There is a significant influence between compensation and motivation together on employee performance as evidenced by the value of Fcount = 42.793> Ftable = 3.16. There is a significant influence between competence on employee performance as evidenced from the tcount = 6.841> ttable = 1.671. There is a significant effect between compensation on employee performance as evidenced by the tcount = 7.098> ttable = 1.671. There is a significant influence between motivation on employee performance as evidenced from the tcount = 6.005> ttable= 1,671.